1978
DOI: 10.2176/nmc.18pt1.119
|View full text |Cite
|
Sign up to set email alerts
|

Meningiomas in Childhood and Adolescence

Abstract: Meningiomas are rare tumors of childhood and adolescence but one should always consider them when making a differential diagnosis. Seventy-five patients in this age group were reviewed, including 7 of our own. Several features differing from those of adulthood meningiomas are described. Some of the tumors may have unusual growth patterns, such as cyst formation, resulting in confusing angiographic appearances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1

Year Published

1980
1980
1994
1994

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
1
12
1
Order By: Relevance
“…Characteristics of meningiomas in childhood as revealed by the present study are generally in accordance with those of other reports [5,6,8,10,12]. The distinct features in the childhood group of meningiomas were: (1) rela tively high incidence in the lateral ventricles (11.1%), (2) high incidence of cyst formation in the tumor (16.7%), and (3) high incidence of cases without any dural attachment (12.5%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Characteristics of meningiomas in childhood as revealed by the present study are generally in accordance with those of other reports [5,6,8,10,12]. The distinct features in the childhood group of meningiomas were: (1) rela tively high incidence in the lateral ventricles (11.1%), (2) high incidence of cyst formation in the tumor (16.7%), and (3) high incidence of cases without any dural attachment (12.5%).…”
Section: Discussionsupporting
confidence: 91%
“…It was reported that the meningioma in the posterior fossa was more frequent in childhood [8,10]. In our series, however, there was no statistically significant difference in its frequency between the childhood and adult groups.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The occurrence of cystic meningiomas in older children or adults is rare [37,38]. Other authors have reported the propensity for 196 Molleston/Moran/Roth/Rich Infantile Meningioma [9] 1961 newborn male 2 months angioblastic + cystic Taptas [10] 1961 4 male 1 month fibroblastic + cystic Vigouroux et al [11] 1964 7 female 24 months not specified Solitäre et al [12] 1964 newborn female dead birth hemangiopericytoma Mendriatta et al [ 13] 1967 4 male alive retarded malignant + cystic Fessard [ 14] 1968 8 male 5 years fibroblastic Koos et al [ 15] 1971 11 male 2 years fibroblastic Sosnik et al [16] 1972 newborn female dead fibroblastic Merten et al [17] 1974 4 male dead fibroblastic Suematsu et al [ 18] 1974 5 male 2 years fibroblastic + cystic Satyanarayana et al [ 19] 1975 6 male 12 days fibroblastic + cystic Bueno et al [20] 1977 8 male dead fibroblastic Numaguchi et al [21] 1978 6 male 2 years fibroblastic + cystic Endo et al [22] 1978 4 female dead fibroblastic Dong et al [23] 1980 6 male dead 14 days fibroblastic + cystic Amano et al [24] 1980 10 male 2 months fibroblastic + cystic Roux et al [25] 1980 6 male 6 years not specified Andras et al [26] 1984 3 female 6 months fibroblastic Katayama et al [27] 1986 5 female 4 months fibroblastic + cystic Piatt et al [28] 1986 6 female 12 months papillary Sakaki et al [5] 1987 11 male 5 years fibroblastic Sakaki et al [5] 1987 8 male 2 years hemangiopericytoma + cystic Lopez et al [29] 1988 intraparenchymal or intraventricular meningiomas in children [39], as well as the tendency for these tumors to occur nearly always supratentorially [28]. Despite the histologic appearance of this patient's tumor, he was not treated with chemotherapy or radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Myelography is of decisive impor tance because it not only enables us to localize the site of the lesion, but in many cases allows us to determine the type of the tumor [1,4,17]. Cerebral angiography is crucial in diagnosing intracranial tumors of child hood [19], but spinal angiography is of secondary importance in the local ization and differentiation of intraspinal tumors, except in cases of heman gioblastoma [20,23]. Though there are some reports of the angiographic demonstration ofintraspinal meningiomas [7,23], and though Spiegel and Koch-Weser [24] state that the technical feasibility and relatively low risk of catheter vertebral angiography have made this a useful procedure in addition to myelography in the preoperative evaluation of extramedullary tumors of the upper cervical region, its diagnostic efficacy is not great.…”
Section: Discussionmentioning
confidence: 99%